The Animal Rescue Club - Himmelman, John. ([New York] : HarperCollins, 1998)
Members of the Animal Rescue Club save wild animals in trouble, nurse them back to health, and return them to the wild.
3.5
3-6
Keywords: Clubs -- Fiction; Wildlife rescue -- Fiction; Animal welfare -- Fiction; Clubs -- Fiction; Wildlife rescue -- Fiction